2011
DOI: 10.1111/j.1365-2958.2011.07568.x
|View full text |Cite
|
Sign up to set email alerts
|

A type III effector protease NleC from enteropathogenic Escherichia coli targets NF‐κB for degradation

Abstract: Many bacterial pathogens utilize a type III secretion system (T3SS) to inject virulence effector proteins into host cells during infection. Previously, we found that enteropathogenic Escherichia coli (EPEC) uses the type III effector, NleE, to block the inflammatory response by inhibiting IκB degradation and nuclear translocation of the p65 subunit of NF-κB. Here we screened further effectors with unknown function for their capacity to prevent p65 nuclear translocation. We observed that ectopic expression of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
138
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(144 citation statements)
references
References 48 publications
5
138
0
1
Order By: Relevance
“…Recently several studies have identified NleC as another effector that suppresses inflammatory response through inhibition of NF-B (3,35,38,56). These studies showed that NleC also suppressed IL-8 release and NF-B activation by cultured epithelial cells, specifically through the degradation of the NF-B p65 subunit.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…Recently several studies have identified NleC as another effector that suppresses inflammatory response through inhibition of NF-B (3,35,38,56). These studies showed that NleC also suppressed IL-8 release and NF-B activation by cultured epithelial cells, specifically through the degradation of the NF-B p65 subunit.…”
mentioning
confidence: 90%
“…These studies showed that NleC also suppressed IL-8 release and NF-B activation by cultured epithelial cells, specifically through the degradation of the NF-B p65 subunit. NleC is a zinc protease that cleaves NF-B p65 subunit (3,35,38,56). Curiously, despite the prominent immunosuppressive role attributed to NleC in vitro, no studies have yet examined the potential for NleC to modulate inflammation in vivo.…”
mentioning
confidence: 99%
“…28 Other NF-κB components, c-Rel and p50, are also degraded in infected cells. 29 As a result, NleC-mediated proteolysis suppresses NF-κB activation and subsequently impairs the secretion of IL-1β, IL-8 and TNF-α. [28][29][30] The NF-κB component p65, recruited by NleC, is targeted for proteasomal-independent degradation, presumably via a consensus zinc metalloprotease motif.…”
Section: Stabilizing Iκb By Inactivating Tab2 and Tab3mentioning
confidence: 99%
“…29 As a result, NleC-mediated proteolysis suppresses NF-κB activation and subsequently impairs the secretion of IL-1β, IL-8 and TNF-α. [28][29][30] The NF-κB component p65, recruited by NleC, is targeted for proteasomal-independent degradation, presumably via a consensus zinc metalloprotease motif. Early studies suggested that the site of p65 cleavage by NleC lies within its N-terminal Rel homology domain (RHD), which is involved in DNA binding by p65 on adjacent, parallel strands.…”
Section: Stabilizing Iκb By Inactivating Tab2 and Tab3mentioning
confidence: 99%
“…For example, NleE is a cysteine methyl transferase that methylates the zinc finger domain of TAB2/3, thereby inhibiting TAB2/3 interaction with ubiquitinated TRAF and blocking the phosphorylation of IκB by the IKK complex and hence the degradation of IκB (Newton et al, 2010;Zhang et al, 2011). NleC and NleD are zinc metalloproteases that cleave the p65 subunit of NF-κB and the MAPKs p38 and JNK, respectively (Baruch et al, 2011;Pearson et al, 2011). NleH has both anti-apoptotic and anti-inflammatory effects acting in part by binding ribosomal protein S3 (Hemrajani et al, 2010;Gao and Hardwidge, 2011).…”
mentioning
confidence: 99%